The Use of Phrases in Writing Recount Textby The Students of SMA Negeri 1 Karanganyar in Academic Year of 2013 - 2014 - , Hidayati; , Agus Wijayanto, Ph. D; , Mauly Halwat, M. Hum. Ph. D (2015)
This study is mainly aimed at finding: (1) The students' ability in writing of phrases in recount text, (2) The types of phrases usually used in recount text by each the student, (3) The constructions of phrase used by the students. The study was carried out at SMA N 1 Karanganyar. The method used was a qualitative descriptive study. This research is conducted to analyze the students' skills in using phrases in writing recount text. The population of this study was tenth grade students of SMA N 1 Karanganyar in the academic year 2013/2014. The writer took 35 students as the sample by using simple random sampling. In collecting the data, the writer used a writing diary test in the form of essay test. They used some phrases in their writing test. Based on the findings, it is concluded that (1) The ability of the tenth grade students of SMA Negeri 1 Karanganyar in academic 2013/2014 in using phrases was good. Their ability was 80%. (2) The tenth grade students of SMA N 1 Karanganyar in academic 2013/2014 used some types of phrases in writing recount text. Namely noun phrase, verb phrase, Adjective phrase, Adverb phrase, and preposition Phrase. The total correctly phrases were 606 and 154 incorrectly. So, we can conclude here that the tenth grade students of SMAN 1 Karanganyar used 760 phrases in writing recount text. (3) The researcher found some constructions of phrases such as the construction of Noun Phrase, Verb Phrase, Adjective Phrase, Adverb Phrase and Preposition Phrase used by the tenth grade students of SMAN 1 Karanganyar in writing recount text. They used 7 constructions of noun phrase, two constructions of verb phrase, adverb phrase and preposition phrase, while they used three constructions of adjective phrase.